Development of a Tool to Identify Patients' Preference for Vitamin K Antagonist or Direct Oral Anticoagulant Therapy - Zolfaghari, Shabnam; Harenberg, Job; Froelich, Lutz; Wehling, Martin; Weiss, Christel (Seminars in Thrombosis and Hemostasis, 2014)
Direct oral anticoagulants (DOACs) were developed for the treatment of thromboembolic diseases to overcome limitations of vitamin K antagonists (VKA). International guidelines on atrial fibrillation acknowledge patients' for antiembolic therapy with VKA or DOAC as relevant decision criteria. The objective assessment of patients' preference social interactions and psychological factors are hard to measure albeit representing important contributors. After a series of structured interviews and pilot studies assessing the preparedness to use DOAC as an anticoagulant and the motivation of patients to participate in clinical studies with DOAC, seven items were identified from several questionnaires by regression analysis. Those items were seen the best to describe the willingness to change anticoagulation from VKA to DOAC. By their use, we aim to develop a tool for the objective identification of the patients' preferences for VKA or for DOAC to increase adherence to therapy and to reduce anticoagulant undertreatment. German-speaking patients were asked to fill out a questionnaire consisting of biographic data and the seven selected items, and 180 patients completed the questionnaire so far. Of these, 90 patients were on treatment with VKA (group 1), 57 patients changed anticoagulation from VKA to DOAC (group 2), 29 patients were DOAC naive patients (group 3), and 4 patients changed from DOAC to VKA (group 4). Overall, 94 patients received VKA, 29 patients received dabigatran, 50 patients received rivaroxaban, and 7 patients received apixaban as an anticoagulant. Eight patients were younger than 40 years, 35 patients were aged between 40 and 59 years, 53 patients were aged between 60 and 70 years, and 84 patients were aged older than 70 years. Indication for anticoagulation were atrial fibrillation (n = 106), pulmonary embolism (n = 24), deep vein thrombosis (n = 40), artificial heart valve replacement (n = 8), or other diseases (n = 2). Based on the results of the analysis, a score will be suggested to identify the preference of patients for anticoagulation with VKA or DOAC. This tool may be useful for practitioners and health-care professionals to support patient adherence to therapy, and thereby increase treatment effectiveness.
Keywords: anticoagulation; preference; adherence; warfarin; dabigatran; rivaroxaban; apixaban; atrial fibrillation